Strategi Pemasaran Sebagai Salah Satu Cara Dalam Meningkatkan Jumlah Pengunjung Pada Taman Mini Indonesian Indah - Prabowo, Agung; Purwanti, Ari (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
Marketing strategy is an activity conducted by firm in the frame of establishing price of product, distribution, and promotion to introduce products or service produced by the firm. Consumers are expected to be interested to make use of those products and services, thereby marketing strategy will bi able to increase visitors. In establishing marketing strategy TMII conducted vision, mission, and goals analysis first before carrying out SWOT analysis by means of regression, correlation, and coefficient of determination analysis.